Necrotising enterocolitis suspicion in newborns with duct-dependent congenital heart disease: prognosis and risk factor - Isabelle Ligi; Caroline Ovaert; Fedoua El Louali; Camille Prom; Belghiti Alaoui Myriem; Celia Gran; Virginie Fouilloux; Marien Lenoir; Fabrice Michel (BMJ Publishing Group, 2024)
Introduction The main risk factors of necrotising enterocolitis (NEC) are prematurity and low birth weight. The aim of our study was to identify risk factors for NEC in patients with duct-dependent congenital heart disease (CHD).Study design Newborns with duct-dependent CHD and NEC were matched 1:1 to those without NEC. Matched criteria were gestational age, birth weight, antenatal versus postnatal diagnosis and type of CHD.Results Twenty-three infants were included in each group. In the NEC group, mortality, length of intensive care unit stay and length of hospital stay were significantly higher (p=0.035; p<0.0001; p<0.0001). Lower diastolic blood pressure (DBP), negative flow balance, peritoneal dialysis and epinephrine-infusion were significantly associated with NEC (respectively, p=0.008, p=0.002, p=0.007, p=0.017). In multivariate analysis, DBP≤30 mm Hg remained the only independent risk factor of NEC (OR=8.70; 95% CI (1.46 to 53.50), p=0.019).Conclusion A DBP lower than 30 mm Hg was in our matched population of newborns with duct-dependent CHD, independently associated with NEC.